2013
DOI: 10.1016/j.cplett.2013.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Amide I band and photoinduced disassembly of a peptide hydrogel

Abstract: Peptide hydrogels are promising candidates for a wide range of medical and biotechnological applications. To further expand the potential utility of peptide hydrogels, herein we demonstrate a simple yet effective strategy to render peptide hydrogels photodegradable, making controlled disassembly of the gel structure of interest feasible. In addition, we find that the high-frequency amide I′ component (i.e., the peak at ~1685 cm−1) of the photodegradable peptide hydrogel studied shows an unusually large enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“… 42 , 43 The latter is a lysine analogue [hereafter termed Lys(nvoc)] with a photolabile hydrophobic moiety and has been used to control the disassembly of peptide aggregates and hydrogels via illumination. 44 , 45 Should Lys8 indeed serve as an aggregation gatekeeper of Trpzip2, we expect that this Trpzip2 mutant (hereafter termed Trpzip2-K) will exhibit a significantly stronger aggregation propensity.…”
mentioning
confidence: 99%
“… 42 , 43 The latter is a lysine analogue [hereafter termed Lys(nvoc)] with a photolabile hydrophobic moiety and has been used to control the disassembly of peptide aggregates and hydrogels via illumination. 44 , 45 Should Lys8 indeed serve as an aggregation gatekeeper of Trpzip2, we expect that this Trpzip2 mutant (hereafter termed Trpzip2-K) will exhibit a significantly stronger aggregation propensity.…”
mentioning
confidence: 99%
“…To demonstrate photoactivity in the opposite direction, we recently showed that modification of two Phe residues in the peptide hydrogel sequence (FKFE) 2 with Lys(nvoc) preserves the ability of the peptide to form a macroscopic hydrogel as shown in the AFM image in Figure 7A. However, these mutations render the formed hydrogel photodegradable in response to light, as indicated in Figure 7B [121]. In a slightly different treatment, Griffin et al [122] utilized an ortho -nitrobenzyl cage as a photodegradable linker to tether a cell-adhesive peptide to a macromer-based hydrogel, thus allowing light-induced release.…”
Section: Manipulating Biological Assemblies With Lightmentioning
confidence: 99%
“…Hydrogels that respond to an exogenous stimulus to temporally modulate hydrogel rigidity and gel-sol/sol-gel transitions are desirable in the development of hydrogels for biomedical applications. 2,8,9 Environmental pH, 10 redox potential, 11 temperature, 12 ionic strength, 13 enzyme activation, 14,15 and light 16,17 have been exploited to promote self-assembly and hydrogel formation. Specically, designed amphipathic peptides containing b-hairpins have been employed to form well-ordered hydrogels that can be reversibly manipulated using pH, 18 temperature, 12,19 and ion complexation.…”
Section: Introductionmentioning
confidence: 99%